TRIFLUOROACETIC ACID CATALYZED ONE-POT FOUR-COMPONENT DOMINO REACTION FOR THE SYNTHESIS OF SUBSTITUTED DIHYDRO 2-OXYPYRROLES - Lashkari, Mojtaba; Taher Maghsoodlou, Malek; Karima, Mahsa; Kangani, Mehrnoosh (Journal of the Chilean Chemical Society, 2018)
Trifluoroacetic acid was applied as an efficient catalyst for the one-pot four-component synthesis of N-aryl/alkyl-3-aminodihydropyrrol-2-one-4-carboxylates via the domino reaction of amines, formaldehyde and dialkyl acetylenedicarboxylates at ambient temperature in methanol. This methodology includes number of advantages such as: short reaction time, clean work-up, use of inexpensive catalyst, high yields and clean work-up. The work-up of this reaction involves only a filtration and a simple washing step with MeOH, and there is no need for column chromatography.